The influence of carbonitriding process on microstructure and mechanical properties of micro-alloyed steel - M. Hazlinger; M. Dománková; K. Kocúrová (Metalurgija, 2013)
The article deals with the analysis of carbonitrided samples of S460MC microalloyed thermo-mechanically treated steel. The steel surface was saturated with carbon and nitrogen at the temperature of 860 °C. The nitrogen-methanole atmosphere with Amonnia addition was used for surface saturation in the process of carbonitriding. Oil hardening and tempering at 200 °C/1 hour followed after the diffusion saturation of experimental steel sample. The surface layer was composed of martensite, retained austenite and fine carbides of alloying elements. This was demonstrated with light microscopy and confirmed by TEM (transmission electron microscope). The paper also presents the results of chemical composition and hardness measurement.